2013
DOI: 10.1016/j.pain.2013.02.003
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, double-blind, placebo-controlled trial of a chemokine receptor 2 (CCR2) antagonist in posttraumatic neuralgia

Abstract: We evaluated the analgesic efficacy, safety and tolerability of a novel chemokine receptor 2 (CCR2) antagonist, AZD2423, in posttraumatic neuralgia. This was a double-blind, randomized, parallel-group, multicentre study. One hundred thirty-three patients with posttraumatic neuralgia were equally randomized to 28days' oral administration of 20mg AZD2423, 150mg AZD2423 or placebo. The primary efficacy variable was the change of average pain score from 5days at baseline to the last 5days of treatment, measured by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(32 citation statements)
references
References 24 publications
0
32
0
Order By: Relevance
“…AZD2423, which is a highly selective antagonist for CCR2, induced robust analgesia in two rodent models of neuropathic pain and a model of joint destruction pain (http://www.ncats.nih.gov/files/AZD2423.pdf). However, AZD2423 did not show significant effects in a trial of posttraumatic neuralgia, despite a there being trend towards a reduction in some sensory components of pain such as paroxysmal pain and paresthesia and dysesthesia 93 . This low efficacy may arise from species selectivity (rodents versus humans), pharmacokinetic properties and/or drug metabolism, and redundancy in the chemokine network, as one chemokine often has more than one receptor.…”
Section: Chemokines: Mediators Of Neuron–glial Interactionsmentioning
confidence: 80%
See 1 more Smart Citation
“…AZD2423, which is a highly selective antagonist for CCR2, induced robust analgesia in two rodent models of neuropathic pain and a model of joint destruction pain (http://www.ncats.nih.gov/files/AZD2423.pdf). However, AZD2423 did not show significant effects in a trial of posttraumatic neuralgia, despite a there being trend towards a reduction in some sensory components of pain such as paroxysmal pain and paresthesia and dysesthesia 93 . This low efficacy may arise from species selectivity (rodents versus humans), pharmacokinetic properties and/or drug metabolism, and redundancy in the chemokine network, as one chemokine often has more than one receptor.…”
Section: Chemokines: Mediators Of Neuron–glial Interactionsmentioning
confidence: 80%
“…This low efficacy may arise from species selectivity (rodents versus humans), pharmacokinetic properties and/or drug metabolism, and redundancy in the chemokine network, as one chemokine often has more than one receptor. Given the important role of central chemokine signalling in chronic pain 23 , the low efficacy of the CCR2 antagonist AZD2423 in a pain trial 93 may also be a result of poor CNS actions. To potentially increase the efficacy of chemokine antagonism it might be beneficial to simultaneously target several chemokine receptors.…”
Section: Chemokines: Mediators Of Neuron–glial Interactionsmentioning
confidence: 99%
“…Consistent with this hypothesis, some studies showed that lidocaine and morphine act differently on the different neuropathic pain symptoms and dimensions assessed with quantitative sensory testing (QST) and/ or specific neuropathic pain questionnaires [2,[3][4][5]. This hypothesis also is supported by a recently published phase 2 study showing that AZDD2423, a novel chemokine receptor 2 antagonist, did not induce significant effects on overall pain intensity, but showed trends toward a greater reduction on the NPSI total score and NPSI dimensions for paroxysmal pain and paresthesia/dysesthesia than placebo [18].…”
Section: Introductionmentioning
confidence: 89%
“…In line with this, several chemokine receptors are constitutively expressed by primary sensory nociceptors or induced in pathophysiological conditions (reviewed in REFS 11,12,15,16). However, most of these data come from preclinical studies, and one recent clinical trial of a CC-chemokine receptor 2 (CCR2) antagonist failed to demonstrate any analgesic efficacy in post-traumatic neuralgia 17 . These immune mediators exert their algesic effects in several ways.…”
Section: Autoantibodiesmentioning
confidence: 97%